REMEDIASI PEMAHAMAN KONSEP TEKANAN HIDROSTATIK MENGGUNAKAN MODEL ECIRR DI SMA NEGERI 1 SUNGAI AMBAWANG - Aboi yarso; Edy Tandililing; Syukran Mursyid P (Universitas Tanjungpura, 2019)
Abstract This study aimed to know the influence of the ECIRR learning model is to remediate students' conceptual understanding of hydrostatic pressure material at SMA N 1 Sungai Ambawang. This research is pre-experimental design with onegroup type pre-test-post-test design. The sample 21 students of experiment class. This partisipants were chosen by intact group. Data collection in the study used 6 essay items. The average normalized gain value or <g> = 0.44 with the medium category indicates that there is an increase in students' conceptual understanding using the ECIRR models. Non-parametric tests were conducted with the Wilxocon Match Paris test with a significant level of 5% indicating that there were significant differences pre-test and post-testusing the ECIRR model.Remediation effectiveness showed by Cohen’d effect size value about 2,44 which is very high according to Cohen. This research is hoped can be the alternative learning model in remediating students' conceptual understanding. Keywords: Remediation, Understanding of Concepts, ECIRR Model, Hydrostatic Pressure